Amorphous carbon nanotube mediated low-temperature synthesis of orange emitting self-assembled europium oxy-carbonate microflower. (April 2019) - Ganguly, D.; Banerjee, D.; Das, B.; Das, N.S.; Ghorai, U.K.; Chattopadhyay, K.K.
Graphical abstract: Highlights: 3-Dimensional sharp-edged microflower like structures of europium oxy-carbonate has been synthesized. The samples were characterized by XRD, FESEM, TEM, FTIR, Raman spectroscopy and PL spectroscopy. A growth mechanism has been proposed for formation of the structure. Samples show efficient PL property in near red region. Abstract: Sharp-edged microflakes and self-assembled microflower structures of europium hydroxycarbonate were synthesized using homogeneous precipitation method. Here for the first time amorphous carbon nanotubes (a-CNTs) were as carbon precursor. Europium Oxycarbonate microflowers were obtained by heating the hydroxyl carbonate sample at 500 °C. The hydroxyl carbonate sample witnessed a splitting of broad flake like structure into sharp edged flower. All the flower and flake like samples were characterized with the help of FESEM, TEM, XRD, FTIR spectroscopy, and Raman analysis. It has been speculated that the rpm rate, related presence of the hydroxyl and carbonate radical and formation of defect induced nucleation sites on the a-CNTs wall are the key reason for the growth of such structure. This has been confirmed from the FESEM images. The sample showed room temperature visible PL spectra in the red region due to 5 D0 → 7 F1 and 5 D0 → 7 F2 transitions of the Eu 3+ ion.